Correction to: Hubungan penguasaan perkalian dan pembagian dasar terhadap prestasi belajar matematika siswa kelas VIII SMP PMDS Putra Palopo - Rahmah, Nur; Asnidar, Asnidar (Jurnal Elemen, 2024)
Correction to: Jurnal Elemen, Vol. 1 No. 1, January 2015, p. 57-69  https://doi.org/10.29408/jel.v1i1.81 The original version of this article unfortunately contained a mistake. The previous email was not the corresponding author’s email, her email is rnur68845@gmail.com. The original article has been corrected. The original article can be found online at https://doi.org/10.29408/jel.v1i1.81